Review of the genus Sobrala Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Alebrini) with description of four new species and a new record from China - Kang, Ju-Xia; Zhang, Ya-Lin (Zootaxa, 2015)
The genus Sobrala Dworakowska is reported for the first time in China and a key to known species of the genus is provided. Four new species, Sobrala acanthophylla, S. dactylina, S. lamellaris and S. quadrilatera spp. nov. from China are described and illustrated.